2017
DOI: 10.1111/cea.12927
|View full text |Cite
|
Sign up to set email alerts
|

IL4Rα and ADAM33 as genetic markers in asthma exacerbations and type‐2 inflammatory endotype

Abstract: IL4RA and ADAM33 variants may be risk markers of asthma exacerbations in type-2 inflammatory endotype. Precise endotyping may facilitate the identification of genetic risk markers of asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Periostin is secreted as a 93.3-kDa extracellular matrix protein [11]. Consistent with previous studies on patients with asthma and the general population [12][13][14][15][16], the present study showed that the serum periostin level was negatively associated with BMI, albeit marginally. This precluded us from using serum periostin as a simple marker to predict severe OSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Periostin is secreted as a 93.3-kDa extracellular matrix protein [11]. Consistent with previous studies on patients with asthma and the general population [12][13][14][15][16], the present study showed that the serum periostin level was negatively associated with BMI, albeit marginally. This precluded us from using serum periostin as a simple marker to predict severe OSA.…”
Section: Discussionsupporting
confidence: 91%
“…Serum periostin, which is an extracellular matrix protein, is a robust marker of T helper type 2 (Th2) inflammation, particularly in asthma [10][11][12]. Interestingly, several recent studies on asthma and the general population have revealed that serum periostin was negatively associated with body mass index (BMI) [12][13][14][15][16] and serum leptin [15]. In addition to Th2 inflammation, periostin has been shown by in vitro studies to be upregulated under several stimulations, including mechanical stress [17] and hypoxic stimulation [18], which are major features of OSA [19].…”
Section: Introductionmentioning
confidence: 99%
“…As the miR‐146a level was reduced in the airway epithelial cells from patients with asthma, we next analyzed mRNA expression of miR‐146a indirect (CXCL1 and IL‐8) [26, 28 ] and direct (IRAK1) [27 ] target genes in the same samples. In addition, to evaluate the relevance of our findings, we assessed the expression of genes previously associated with Th2 type immune responses, including IL‐33 [32 ] and IL‐4 receptor (IL‐4R) [33 ], and the interferon‐response genes associated with Th1 type immune responses, such as interferon regulatory factor 1 (IRF1) and IFITM1. Among these genes, only the expression of IL‐33 was detected to be increased when all asthma patient samples were included to analysis (Additional file 1 : Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study revealed that the expression levels of ADAM33 were upregulated in the lung tissues of asthma patients (12). In another study, in situ hybridization and immunohistochemistry were used to determine the mRNA and protein expression levels of ADAM33 in human bronchial biopsy specimens, and the results indicated that ADAM33 was significantly overexpressed in tissues from asthmatic patients compared with those from normal subjects (13).…”
Section: Discussionmentioning
confidence: 96%